Just Words: Intentions, Tolerance and Lexical Selection*. (Philosophy & Phenomenological Research, 2022)
We all make mistakes in pronunciation and spelling, but a common view is that there are limits beyond which a mistaken pronunciation or spelling becomes too dramatic to be recognized as of a particular word at all. These considerations have bolstered a family of accounts that invoke speaker intentions and standards for tolerance as determinants of which word, if any, an utterance tokens. I argue this is a mistake. Neither intentions nor standards of tolerance are necessary or sufficient (individually or jointly) for determining which word an utterance tokens. Instead, drawing in part on empirical research on word production, I offer an alternative account, Originalism‐plus‐Transfer (OPT), according to which word tokening depends entirely on lexical selection during word production, and on how the selected lexical item is situated within the network of causal/historical connections leading back to its neologizing. Once the elements of my account are in place, as a bonus, we will have resources for a promising answer to the question of word individuation as well.